Uji karakteristik briket campuran serbuk kayu dan tandan kosong Sawit sebagai bahan bakar alternatif - La Ode Ahmad Barata; Masharib Al Akhyar; Aminur; Amrullah; Akbar Naro Parawangsa (Program Pendidikan Vokasi Teknik Mesin, 2024)
Advances in technology made the use of fossil fuels a major issue, while the sources of fossil fuels continue to decrease due to their perishable nature. Biomass, including waste such as sawdust and oil palm empty fruit bunches, has potential as an alternative energy source that can be converted into briquettes. This study aims to determine the characteristics of biomass sawdust and oil palm empty fruit bunches as briquette materials as an alternative to fossil fuels. This research was conducted experimentally to determine the optimal formulation of a mixture of Wood Powder (SK) and Empty Palm Bunches (TKKS) in making briquettes. Composition variations tested include 100% SK, 100% TKKS, 50% SK: 50% TKKS, 70% SK: 30% TKKS, 30% SK: 70% TKKS. The results showed that the ultimate and proximate characteristics of 100%SK and 100%TKKS have good fixed carbon content. Based on the heating efficiency test, the best value is with the composition of 100% SK with 10% starch adhesive getting a combustion efficiency value of 7.65%. The best porosity index was obtained in the formulation of 70% SK: 30%TKKS with a value of 1.52%, while the best durability index is in briquettes with a composition of 100%TKKS with 10% starch adhesive getting a value of 0.12%. The briquette properties of sawdust and empty palm kernel can be the initial data in the development and use of biomass briquettes or co-firing fuel for industrial furnace because it has good mechanical and physical properties. Thermal efficiency test in the field should use biomass stoves to obtain accurate biomass performance data.